Developing Countries and a New Round of WTO Negotiations - Hertel, Thomas W. (World Bank, Washington, DC, 2014)
This article summarizes some of the results and findings emerging from an ongoing World Bank a research and capacity-building project that focuses on the World Trade Organization (WTO) negotiating agenda from a developing country perspective. Recent research suggests that the potential gains from further multilateral liberalization of trade remain very large. The payoffs associated with attempts to introduce substantive disciplines in the WTO on domestic regulatory regimes are much less certain. This suggests that the focus of current and future negotiations should be primarily on the bread and butter of the multilateral trading system-the progressive liberalization of barriers to trade in goods and services on a nondiscriminatory basis. In addition, priority should be given to ensuring that rules are consistent with the development needs of poorer countries and to helping developing countries implement WTO obligations.